Hep B Moms: A cross‐sectional study of mother‐to‐child transmission risk among pregnant Asian American women with chronic hepatitis B in New York City, 2007‐2017. Issue 2 (27th November 2019) - Lyu, Janice; Wang, Su; He, Qingqing; Pan, Calvin; Tang, Amy S.
Abstract: Mother‐to‐child transmission (MTCT) is responsible for the majority of chronic hepatitis B virus (HBV) infections worldwide. Despite timely HBV immunoprophylaxis of neonates, MTCT can occur in infants born to mothers with high levels of HBV viremia. We performed a retrospective cross‐sectional analysis of Asian American women with chronic HBV evaluated with HBV DNA during prenatal care at two community health sites in New York City from 2007 to 2017. We described patient's demographic and clinical characteristics, categorized their HBV disease phase and analysed for variables associated with high MTCT risk (defined by HBV DNA level >200 000 IU/mL) using multivariable logistic regression. A total of 1298 pregnancies among 1012 mostly China‐born (97.6%) women with chronic HBV were included in the study. Of the 1241 pregnancies among women not on antiviral treatment, 22.4% were considered high risk for MTCT and, of these, 255 (91.7%) were HBV e antigen (HBeAg)‐positive and 19 (6.8%) were HBeAg‐negative. HBeAg‐positive status and ALT levels between 26 and 50 U/L were associated with higher likelihood for being high risk for MTCT. Only 0.8% of pregnancies low risk for MTCT were in the immune active phase while the majority (58.4%) were in the inactive chronic HBV phase of infection. Approximately one in five (22.4%) pregnancies among Asian American women with chronic HBV was considered high risk for MTCT and met criteria for antiviral therapy. Full assessment of HBV pregnant women and early coordinated care is needed to deliver interventions to prevent MTCT during critical windows of time.